“La mujer sin territorio”: un análisis sobre los roles de género en la obra pictórica de Remedios Varo - Jauler Doria-Medina, María Jesús (2023)
The Spanish painter Remedios Varo, one of the female most iconic figures of the pictorial surrealistic movement, participated in the European movement form the first half of the twentieth century for several years, until she migrated to Mexico where she developed her most famous artistic production. Varo’s  work is distinguished by female characters of magical, fantastic, and oneiric qualities who are in a constant search for freedom. These subjects move between confinement and liberation, often without a vehicle and limited in their own movement. The main objective of this article is to analyze the ways in which gender roles are embodied in women in the painting Capillary Locomotion from 1959, as well as to explore the concepts of violence and male domination. The painting presents a female subject without territory or capacity for movement, who moves across the space only by her connection with men, often in a violent way.